KNOWLEDGE MANAGEMENT APLIKASI PENGOLAHAN JADWAL PERKULIAHAN PROGRAM STUDI SISTEM INFORMASI ISTN - Indah Puspitasari Lubis; Marhaeni Marhaeni (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2020)
In a university, there must be lecturers and students. Lecturers at a university have different teaching schedules between one lecturer and another, so even with students they will not be able to take courses at the same time. If the lecturer or student schedule is not well arranged, the schedule will be messy. At the National Institute of Science and Technology in particular the Information Systems Study Program has used a computerized system in the lecture process, but its use is still limited. Here we will create a Knowledge Management application that is processing lecture schedules using Visual Basic Net and SQL Server 2005 Database. By designing the system using UML (Unified Modeling Language) with database design obtained by several table structures. The result is an application program for knowledge management for scheduling special lectures in the Information Systems study program. This lecture scheduling system functions to manage lectures in the information system study program, this system is made to produce a combination of course pairs and lecturers as a whole. Keywords: Knowledge Management, Schedule Processing Application, UML